Korelasi Aktivitas Belajar Siswa di Luar Kelas dengan Evaluasi Hasil Belajar Fikih di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru - Nurhadi, Nurhadi (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study stood out of two variables, namely learning activities as X variables (independent / independent variables) and student learning outcomes in Jurisprudence subjects as Y variable (dependent variable). The purpose of this study was to find out the learning activities and student learning outcomes as well as the relationship between learning activities and student learning outcomes in Jurisprudence subjects at the Al-Muttaqin Tsanawiyah Madrasah in Pekanbaru. The subjects of this study were students of the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. While the object of this research is the correlation of learning activities outside the classroom and evaluation of student learning outcomes on fiqh subjects in the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. The population of all students amounted to 385 people, with a sample of students of class VII and VIII which numbered 80 people. Data collection uses questionnaires, observation, and documentation. Based on data processing, the results showed that learning activities at the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru were in the